Changes and Potential Possibilities with the Introduction of Liberos in Men's world class volleyball - Zimmermann, B. (The Coach, 1999)
The introduction of a libero, a "specialized defensive player" is one of the series of innovations categorized in the current official rules of the International Volleyball Association existing for over 100 years. From the vast number of alterations, above all in the 1990s, the libero belongs without a doubt together with the new scoring system to the most important changes in the history rules of our sport. Already tried and tested in the international league and Grand Prix 1998 the libero also celebrated its debut at the world championships in Japan in the same year. Strengthening defensive play was intended owing to the decision made by the FIVB. Spectacular defensive actions should make the game more attractive by an increased part involving long lasting movements, making it more interesting for the spectators and simultaneously opening up chances for smaller players to reach a world class level by using this function. In order to ascertain what extent these objectives have been fulfilled and which alterations are already in force, selected results from analysis of the men's world championships should be considered. The variety of application possibilities which produces the libero play supplements these contributions which should help to ease the introduction of the concept of play to the team. Irrespective of current differing opinions and views the libero can be recommended to explore the ins and out of possibilities and limitations and exploit the advantages of the single game.